Identification and Characterization of Ribosomal Protein S8 Gene of Jute (Plant Tissue Culture and Biotechnology, 2010)
Identification and confirmation of ESTs (expressed sequence tags) corresponding to genomic clones is one of the most important steps in the identification of genes. In this regard, computational approaches such as ab initio and homology based searches using NCBI web portal, together with common laboratory approaches - PCR, RT-PCR and DNA sequencing were used to identify jute ESTs from a jute genomic library. Using degenerate primer-based gene walking from a computationally identified and experimentally verified jute EST, this study has led to the identification of the full length sequence of a jute gene, namely ribosomal protein S8. The sequence of this gene was found to be similar to ribosomal protein S8 gene of related species like Hibiscus macrophyllus, Gossypium hirsutum etc. and that of other species like Carica papaya, Arabidopsis thaliana etc. This gene was further characterized for determining its cellular location to the chloroplast.      Key words: Identification, Characterization, Ribosomal protein S8, Jute D.O.I. 10.3329/ptcb.v19i2.5438 Plant Tissue Cult. & Biotech. 19(2): 207-215, 2009 (December)